Identification of differentially expressed protein in trunking and non-trunking sago palm leaves - Maswida, binti Mustafa Kamal (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Sago palm (Metroxylon sagu Rottb) is a tropical starch crop grown commercially in plantations in Malaysia, especially in Sarawak, as it contains a large amount of starch in its trunk. However, non-trunking phenomenon has been observed to be one of major factor limiting the yields of sago palm starch in Mukah, Sarawak. In this study, proteomics approach was used to investigate differences between trunking and non-trunking proteins in sago palm leaves tissues. Sixteen years old trunking and non-trunking sago palm leaves from deep peat area were extracted with phenol extraction-ammonium acetate/ methanol precipitation. Total protein were subjected to two-dimensional gel electrophoresis (2-DE) coupled with Matrixassisted laser desorption/ionization-time of light/time of flight mass spectrometry (MALDITOF/TOF MS), Reverse phase-high performance liquid chromatography (RP-HPLC) and Nuclear Magnetic Resonance (NMR). Two dimensional gel electrophoresis and MALDITOF/TOF MS analysis and database search has identified ten proteins representing five different protein families namely phosphoglycerate kinase-like, putative ascorbate peroxidase, harpin binding protein, protein disulfide isomerase, and ribulose 1,5-biphosphate carboxylase/oxygenase (RuBisCo) large subunit, three from trunking and two from nontrunking respectively. As for the other five proteins, two proteins were identified as the same proteins as RuBisCo while another three are unknown proteins. Meanwhile, the result from RP-HPLC and NMR showed that both trunking and non-trunking proteins have general similarity but particularly differ in some of the region. It was proposed that the differences found between trunking and non-trunking proteome may correlate to their physicals differences.